2008
DOI: 10.1002/qsar.200760177
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Study on Piperidinecarboxamides as Antiretroviral Agents: An Insight Into the Structural Basis for HIV Coreceptor Antagonist Activity

Abstract: Chemokines receptors have emerged as important drug targets for the development of agents against the Human Immunodeficiency Virus (HIV)/AIDS pandemic. With the purpose of designing new chemical entities with enhanced antiretroviral potencies, the Quantitative Structure -Activity Relationships (QSAR) study carried out on 122 novel piperidin-4-carboxamide derivatives as antagonists of HIV Chemokine Receptor 5 (CCR5) coreceptor binding is presented. The developed model was validated by standard QSAR parameters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The cross-validation analysis was performed using the leave-one-out (LOO) method where one compound is removed from the data set and its activity is calculated using the model derived from the rest of the data set. Statistical significance of the regression equations were tested on the basis of conventional regression coefficient (r 2 ) (Hawkins et al, 2003), Fischer's ratio (F) (Dessalew, 2008), and the standard error of estimate (s) (Dessalew, 2009). The PLS regression method carries out regression using the latent variables from the independent and dependent data that are along their axes of the greatest variation and are most highly correlated (Paliwal (Cramer, 1993).…”
Section: Data Set Preparation and Statistical Analysesmentioning
confidence: 99%
“…The cross-validation analysis was performed using the leave-one-out (LOO) method where one compound is removed from the data set and its activity is calculated using the model derived from the rest of the data set. Statistical significance of the regression equations were tested on the basis of conventional regression coefficient (r 2 ) (Hawkins et al, 2003), Fischer's ratio (F) (Dessalew, 2008), and the standard error of estimate (s) (Dessalew, 2009). The PLS regression method carries out regression using the latent variables from the independent and dependent data that are along their axes of the greatest variation and are most highly correlated (Paliwal (Cramer, 1993).…”
Section: Data Set Preparation and Statistical Analysesmentioning
confidence: 99%
“…Aher et al [20] reported their 3D-QSAR study on analog 4 using comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA) methods realized in SYBYL7.1. More recently, another 3D-QSAR study on this series of antagonists was done by Dessalew [21], using an integrated analysis package, TSAR3.3. Afantitis et al [22] applied multiple linear regression analysis on analog 4 and developed a linear QSAR model.…”
Section: Entry Inhibitorsmentioning
confidence: 99%
“…AIDS has been recognized as a fatal pathogenic disease caused by a retrovirus of the lentivirus family, Human Immunodeficiency Virus (HIV) [3]. The number of HIV-infected subjects keeps alarmingly on the rise [4,5]. The pandemic spread of this disease has prompted an unprecedented scientific and clinical effort to understand and combat it [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the combination therapy [9 -12] has been found to reduce HIV RNA to undetectable level, rescue CD4 þ cell counts, and decrease HIV-related death rate. Despite these results, the cost of therapy is high [13], oral bioavailability is limited [12], and the emergence of multidrug resistance and considerable side effects [14] is considered to be a significant problem, which may lead to failure of eradication of the virus from latently and chronically infected cells for long-term treatment of AIDS [4,15]. Thus, there is a constant and urgent need to develop more effective and less toxic inhibitors for novel therapies [13].…”
Section: Introductionmentioning
confidence: 99%